Memory of the Heart: Visions about the Human Heart from the Experience of the Transplant - Craice De Benedetto, Maria Auxiliadora; Vitorino Vieira, Nadia; Claramonte Gallian, Dante Marcello (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
The meaning attributed to the heart throughout history is ahead of the material dimension, which apparently predominates nowadays to achieve a moral and spiritual greatness, which made the heart occupy a central role. In this study, we sought to delve into visions and meanings attributed to the human heart, having been assessed to what extent there was a real acceptance and incorporation of scientific discourse. Data were collected by interviews conducted according to the approach of the Oral History of Life (thirty heart recipients, ten family members and ten professionals with experience in the area were interviewed). The texts generated from the interviews were analyzed using immersion/crystallization techniques, inspired by Hermeneutic Phenomenology. The following major themes were revealed: gratitude, spirituality, rebirth, no allusion to the threat of imminent death present before transplantation, polarity on the meaning of the heart.